WITHHOLDING TAX ATAS BUNGA DALAM TRANSAKSI FINANCIAL TECHNOLOGY LENDING - Sulfan Sulfan (Politeknik Keuangan Negara STAN, 2019)
ABSTRACTFintech Lending in Indonesia is developing very rapidly which is marked by the accumulation of loans up to June 2019 reaching Rp44.8 trillion. Borrowers are generally individuals and Micro, Small and Medium Enterprises (MSMEs) with a total of 9.7 million borrowers. There are indications of problems with taxation of interest income in the withholding tax mechanism. The purpose of this study is to get an idea of the extent of the Fintech Lending business process so that it is known to the parties who are obliged to withhold Article 23/26 Income Tax on interest income in the withholding tax mechanism. This study concludes that there are difficulties in applying the mechanism of withholding tax through withholding income tax Article 23/26 so that it can be proposed to be subject to final taxation of interest income in Fintech Lending transactions. ABSTRAKFintech Lending di Indonesia berkembang sangat pesat yang ditandai akumulasi pinjaman sampai dengan Juni 2019 mencapai Rp44,8 triliun. Umumnya peminjam adalah perorangan dan Usaha Mikro, Kecil, dan Menengah (UMKM) dengan total 9,7 juta peminjam. Terdapat indikasi permasalahan pengenaan pajak atas penghasilan bunga dalam mekanisme withholding tax. Tujuan penelitian ini untuk mendapat gambaran sejauhmana proses bisnis Fintech Lending sehingga diketahui pihak-pihak yang berkewajiban sebagai pemotong PPh Pasal 23/26 atas penghasilan bunga dalam mekanisme withholding tax. Penelitian ini menyimpulkan bahwa terdapat kesulitan penerapan mekanisme withholding tax melalui pemotongan PPh Pasal 23/26, sehingga dapat diusulkan untuk dikenakan pemajakan yang bersifat final atas penghasilan bunga dalam transaksi Fintech Lending.